Instant technique improvement - visual immediate feedback system
The Visual Immediate Feedback System (VIFS; Virtual Reality Goggles) - the latest technology - allows its users to decrease the delay time between video filming and feedback down to zero and enables the athlete to see himself/herself while performing sporting exercise in real-time.